A Comprehensive Experimental Guide to Studying Cross‐Presentation in Dendritic Cells In Vitro. (14th December 2020) - Sadiq, Barzan A.; Mantel, Ian; Blander, J. Magarian
Abstract: Cross‐presentation was first observed serendipitously in the 1970s. The importance of it was quickly realized and subsequently attracted great attention from immunologists. Since then, our knowledge of the ability of certain antigen presenting cells to internalize, process, and load exogenous antigens onto MHC‐I molecules to cross‐prime CD8 + T cells has increased significantly. Dendritic cells (DCs) are exceptional cross‐presenters, thus making them a great tool to study cross‐presentation but the relative rarity of DCs in circulation and in tissues makes it challenging to isolate sufficient numbers of cells to study this process in vitro. In this paper, we describe in detail two methods to culture DCs from bone‐marrow progenitors and a method to expand the numbers of DCs present in vivo as a source of endogenous bona‐fide cross‐presenting DCs. We also describe methods to assess cross‐presentation by DCs using the activation of primary CD8 + T cells as a readout. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Isolation of bone marrow progenitor cells Basic Protocol 2 : In vitro differentiation of dendritic cells with GM‐CSF Support Protocol 1 : Preparation of conditioned medium from GM‐CSF producing J558L cells Basic Protocol 3 : In vitro differentiation of dendritic cells with Flt3L Support Protocol 2 : Preparation of Flt3L containing medium from B16‐Flt3L cells Basic Protocol 4 : Expansion of cDC1s in vivo for use in ex vivo experiments Basic Protocol 5 : Characterizing resting and activated dendritic cells Basic Protocol 6 : Dendritic cell stimulation, antigenic cargo, and fixation Support Protocol 3 : Preparation of model antigen coated microbeads Support Protocol 4 : Preparation of apoptotic cells Support Protocol 5 : Preparation of recombinant bacteria Basic Protocol 7 : Immunocytochemistry immunofluorescence (ICC/IF) Support Protocol 6 : Preparation of Alcian blue‐coated coverslips Basic Protocol 8 : CD8 + T cell activation to assess cross‐presentation Support Protocol 7 : Isolation and labeling of CD8 + T cells with CFSE